The hardware destruction issue. Issue 7 (July 2021) - Benham, Harry
Abstract : Covid-19 has accelerated change exponentially across a wide range of industries, transforming the way that people work and live, with the technology industry at the forefront. A McKinsey global survey of executives last year concluded that responses to the pandemic had speeded up the adoption of digital technologies by several years, pushing companies over the technology tipping point and transforming business forever. 1